The Lonely Mouse – Single Housing Affects Serotonergic Signaling Integrity Measured by 8-OH-DPAT-Induced Hypothermia in Male Mice - Kalliokoski, Otto (PLoS One, 2014)
Male BALB/c mice single-housed for a period of three weeks were found to respond with a more marked hypothermia to a challenge with a selective serotonergic agonist (8-OH-DPAT) than their group-housed counterparts. This effect of single housing was verified by screening a genetically heterogeneous population of male mice on a C57BL/6 background from a breeding colony. Enhanced activity of the implicated receptor (5-HT(1A)) leading to an amplified hypothermic effect is strongly associated with depressive states. We therefore suggest that the 8-OH-DPAT challenge can be used to demonstrate a negative emotional state brought on by e.g. long-term single housing in male laboratory mice. The study emphasizes the importance of social housing, and demonstrates that male mice deprived of social contact respond with altered serotonergic signaling activity. Male mice not only choose social contact when given the option, as has previously been shown, but will also, when it is deprived, be negatively affected by its absence. We propose that the 8-OH-DPAT challenge constitutes a simple, but powerful, tool capable of manifesting the effect of social deprivation in laboratory mice. It potentially allows not only for an unbiased, biochemical evaluation of psychological stressors, but may also allow for determining whether the effect of these can be counteracted.